Crisis Situations in Enterprises – Symptoms and Expected Support - Styś, Aniela (Publishing House of Wroclaw University of Economics and Business, 2023)
The monograph presents the results of research on specific ways in which various crisis situations are perceived by market entities. Such situations create micro-macro imbalance, being the source of various threats, such as depreciated market position, changed relationships inside the organizations, or sometimes even illegal activities. A number of remedies and actions that could be undertaken to minimize the effects of such threats have been discussed, including not only some changes inside the business entity, but also in education, in terms of its internationalization.
Styś, A. (2023). Crisis Situations in Enterprises – Symptoms and Expected Support. In A. Styś (Ed.), Reactions of Market Entities to Crisis Situations (pp. 21–35). Wroclaw: Publishing House of Wroclaw University of Economics and Business.
Keywords: market entities; crisis situations; threats; behaviour patterns; micro-macro imbalance